Exploring the Incidence and Risk Factors of Diabetic Nephropathy in Type 1 Diabetes: Insights from a Retrospective Cohort Study in Northwest China - Du Z; Liu X; Zhang L; Zhao H; Tian L (Diabetes, Metabolic Syndrome and Obesity)
Zouxi Du,1,2,* Xiaoning Liu,3,* Leyuan Zhang,4 Hui Zhao,5,6 Limin Tian1,7 1The First School of Clinical Medicine, Lanzhou University, Lanzhou, Gansu, People’s Republic of China; 2Department of Endocrinology, Gansu Provincial Hospital, Lanzhou, Gansu, People’s Republic of China; 3Department of Epidemiology and Health Statistics, School of Public Health, Lanzhou University, Lanzhou, Gansu, People’s Republic of China; 4The First Clinical College, Gansu University of Traditional Chinese Medicine, Lanzhou, Gansu, People’s Republic of China; 5College of Integrated Traditional Chinese and Western Medicine, Gansu University of Traditional Chinese Medicine, Lanzhou, Gansu, People’s Republic of China; 6Department of Nephrology, Gansu Provincial Hospital, Lanzhou, Gansu, People’s Republic of China; 7Department of Endocrinology, Sichuan Provincial People’s Hospital, University of Electronic Science and Technology of China, Chengdu, Sichuan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Limin Tian, The First School of Clinical Medicine, Lanzhou University, Lanzhou, Gansu, 730000, People’s Republic of China, Email tlm7066@sina.comPurpose: The study aimed to investigate the incidence of diabetic nephropathy (DN) and their relationship with certain risk factors in patients with type 1 diabetes (T1D) across hospitals in Gansu Province, China.Methods: There were 434 T1D patients recruited from Gansu Province, China, in the present retrospective cohort study between January 2016 and December 2024. Patients were divided into two groups: (i) patients with T1D but without DN and (ii) type 1 diabetic nephropathy (T1DN). Eligibility for T1DN patients included a T1D diagnosis coupled with urine albumin to creatinine ratio ≥ 30 mg/g. Lifetable method helped determine the cumulative T1DN incidence, and Cox regression helped analyze the associated risk factors. The correlation between predictors (eg, age, serum creatinine (Scr)), and T1DN was assessed with restricted cubic spline curves depending on Cox proportional hazards regression models.Results: The five-year cumulative incidence of T1DN was 29.89%. T1DN risk factors included diabetic ketosis/ketoacidosis (hazard ratio (HR): 1.623, 95% confidence interval (CI): 1.099– 2.454, P =0.015) and high Scr levels (HR: 1.003, 95% CI: 1.001– 1.006, P =0.010). However, age (HR: 0.534, 95% CI: 0.306– 0.710, P < 0.001) and high-density lipoprotein cholesterol (HDL-C) (HR: 0.528, 95% CI: 0.261– 0.851, P =0.013) showed a negative association. Significant relationships were not observed with other variables studied, including hypertension, fasting plasma glucose, and postprandial glucose. The dose-response relationship suggested that age, HDL-C, and Scr levels were non-linearly associated with five-year cumulative DN incidences in patients with T1D.Conclusion: Younger age and lower HDL-C levels were identified as risk factors for DN in patients with T1D. Additionally, diabetic ketosis/ketoacidosis and elevated Scr levels were associated with increased DN risk. Early diagnosis and treatment of dyslipidemia are warranted in patients with T1D. Furthermore, close monitoring of patients with diabetic ketosis/ketoacidosis or high Scr levels is crucial for DN management in these patients.Keywords: cumulative incidence, risk factors, type 1 diabetes, type 1 diabetes nephropathy